1994
DOI: 10.1007/bf02917227
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous excretion and true absorption of cobalt as affected by the oral supply of cobalt

Abstract: At the end of a 49-d experiment with 32 growing male rats, a period of 8 d was used to determine endogenous excretion and true absorption as well as apparent absorption and retention of cobalt with the aid of the isotope dilution technique. For this purpose, a single im dose of 58Co was applied at d 35 of the experiment. After that, urine and feces were collected separately from d 8 to 15 after injection of the isotope. The specific cobalt activity of the liver was used as an endogenous reference source. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Absorbed cobalt is primarily excreted though the urine [ 39 ]. Cobalt concentrations were extremely low and not detectable in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Absorbed cobalt is primarily excreted though the urine [ 39 ]. Cobalt concentrations were extremely low and not detectable in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine, Se and Co serum concentrations show a good response to dietary supplementation (Franke et al, 2009;Sch€ one et al, 2009;Cook and Green, 2010). The homoeostatic control of these elements is mainly mediated by urinary excretion: they are absorbed from the intestinal tract at high rates without a homoeostatic control (Kirchgessner et al, 1994(Kirchgessner et al, , 1997(Kirchgessner et al, , 1999. Mineral concentrations in milk are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Absorbed Co is primarily excreted by urine but small amounts appear to be excreted by endogenous Co recycling into digestive tract (Kirchgessner et al, 1994). Absorbed Co is primarily excreted by urine but small amounts appear to be excreted by endogenous Co recycling into digestive tract (Kirchgessner et al, 1994).…”
Section: Excretion Of Cobaltmentioning
confidence: 99%
“…In laboratory animals such as rats and mice, the reported apparent absorption of Co from Co-chloride was in a range 13 to 34 % whereas Co from insoluble Co oxide showed 1 to 3 % absorption rate only (Kirchgessner et al, 1994;. In rats and guinea pigs it has been suggested that Co absorption may decline with age (Naylor and Harrison, 1995).…”
Section: Absorptionmentioning
confidence: 99%
See 1 more Smart Citation